Developing Project-Based-Learning (PBL) Speaking Syllabus for Flight Attendant School in Flipped Learning Network (FLN) Activities - Atika Kumala Dewi; Nur Mukminatien (Pusat Riset dan Inovasi Nasional, 2023)
This article defines the process for developing a speaking syllabus for flight attendant school in a Flipped Learning Network (FLN), which increases student engagement and learning by assigning watching videos at home followed up in pre-teaching discussions, and requiring the students to work on live practices in face-to-face classroom activities. Considering that the syllabus is designed to develop the students' oral competence, the target speaking skill is aimed toward developing students' ability to engage in procedural communication in the workplace. Therefore, the topics/themes are chosen to meet the needs of flight attendants consistent with Project-Based Learning (PBL) by Forum Group Discussions (FGDs). In order to achieve this objective, the development of a syllabus begins with a need analysis, topic selection, syllabus prototype production, expert evaluation, and revision for the final product. The syllabus is organized such that the learning experience is explicitly stated for two formats: online meeting (through Google Classroom for the video analysis) as the lecture homework for pre-discussions followed by classroom face-to-face meeting (through FGDs with peers, individual work, and the teacher) to comprehend students' understanding though some units. Each unit has 2 (two) topics. Each topic consists of 60 (sixteen) minutes or 1 (one) meeting. This syllabus development is considered to be implemented in terms of FLN for instructional activities in flight attendant school resulting higher-order thinking skills such as collaboration, design and problem solving as students tackle difficult problems, work in groups, research, and construct knowledge with the help of the teacher and peers.